How Banksy saved art history - Grovier, Kelly 1968- (Thames & Hudson, 2024)
"Traces art history through Banksy's lens, presenting many of his most recognizable works: from his droll lampooning of the Lascaux cave paintings to his reinvention of Monet's enchanting water-lily pond, a reboot of Géricault's tragic gut-wrenching vision to Vermeer's girl now instilled with street cred, everyone's genius is grist for his unmerciful mill."
Keywords: Banksy -- 1974-; Art / History / 21st century; Banksy / Influence